Heavy metals tolerance on seed germination and growth of serpentine plant species Alyssum murale L. - Gashi, Bekim; Osmani, Mirsade; Berisha, Naim; Buqaj, Liridon; Dakaj, Besnik; Qazimi, Eliesa; Çoçaj, Erëza (Acta Biologica Szegediensis, 2023)
Alyssum murale L. is a nickel hyperaccumulator herbaceous perennial species in a natural serpentine soil and adapted to arid, infertile soils. The objective of this study was to investigate how the seed germination, root, and hypocotyl growth of this plant species respond to exposure to different concentrations of heavy metals such as lead (Pb), cadmium (Cd), nickel (Ni), chromium (Cr) and manganese (Mn). The highest germination, even higher than in the control group, was observed at lower concentrations of Ni, Cd, Pb and Mn, while almost all higher concentrations of the metals decreased germination. Germination time was significantly slower (from about 6 to 10 days) for seeds treated with higher metal concentrations, especially Mn, Cd and Ni, and faster (from about 3 to 5 days) for seeds treated with lower concentrations. The strongest inhibitory effect on root and hypocotyl length occurred in treatments with different concentrations of Pb, Cd, and Mn, and seeds treated with lower concentrations of Ni showed a positive effect on root and hypocotyl growth. Seeds treated with Ni showed relatively high tolerance to this metal, presenting the potential for practical use in various fields of phytoremediation technology.